Possibilities of Legal Regulation of the Conservation of Sacred Places within the Cultural Landscape: The Case of the Republic of Kazakhstan - Farida Mussatayeva; Kuralay Yermagambetova; Saira Shamakhay; Zhazira Baisarina; Tolganay Mustafina (Journal of Islamic Thought and Civilization, 2024)
In recent years, there has been growing attention to the preservation of sacred sites and understanding their significance within the cultural landscape of the Republic of Kazakhstan.  This renewed interest is driven by a revival of national historical and cultural values. The study is relevant since sacred spaces affect the formation of objective historical memory, which is an important component of the national identity. This, in turn, contributes to the consolidation of the people and ensures the national security of the state. The article aims to propose measures (recommendations) to improve legal regulation and preserve the sacred places of the cultural landscape of Kazakhstan. To achieve these objectives, the authors employed methods of theoretical generalization, structural-logical analysis, and synthesis, as well as the method of expert survey. The paper identifies the main problems in the implementation of legal norms for the conservation of cultural landscapes and suggests potential solutions to overcome these challenges. It also outlines measures to increase public participation in the preservation of the cultural landscape. This study concludes that it is necessary to popularize knowledge about the specific features of sacred places in a particular region, develop a program for the preservation of the cultural landscape, and advise residents on the methods and means of preserving sacred places.